2018
DOI: 10.1111/imm.12915
|View full text |Cite
|
Sign up to set email alerts
|

The role of salt for immune cell function and disease

Abstract: The immune system evolved to protect organisms from invading pathogens. A network of pro- and anti-inflammatory cell types equipped with special effector molecules guarantees efficient elimination of intruders like viruses and bacteria. However, imbalances can lead to an excessive response of effector cells incurring autoimmune or allergic diseases. An interplay of genetic and environmental factors contributes to autoimmune diseases and recent studies provided evidence for an impact of dietary habits on the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 110 publications
(272 reference statements)
1
32
0
Order By: Relevance
“…Limitations in accurate measurement of NaCl levels and in the identification of the specific effect of salt independently of other dietary components may account for these controversial results [as discussed in (163)]. Since moderate increases in salt intake has proven to affect human immune cells, including T cells in vivo (26,37), more specific analysis are needed to establish the role of NaCl in human autoimmune disease.…”
Section: The Effect Of Salt In Treg Plasticitymentioning
confidence: 99%
See 1 more Smart Citation
“…Limitations in accurate measurement of NaCl levels and in the identification of the specific effect of salt independently of other dietary components may account for these controversial results [as discussed in (163)]. Since moderate increases in salt intake has proven to affect human immune cells, including T cells in vivo (26,37), more specific analysis are needed to establish the role of NaCl in human autoimmune disease.…”
Section: The Effect Of Salt In Treg Plasticitymentioning
confidence: 99%
“…Whereas, genetic factors clearly predispose to autoimmune development, the dramatic increase in the incidence of autoimmune diseases in Western countries suggests Western lifestyle patterns as important triggers of disease [reviewed in (21,22)]. A variety of factors have been proposed to favor autoimmune development such as decrease pathogen exposure, smoke, hormones, stress, pollutants, dietary components and obesity (23)(24)(25)(26)(27). Moreover, increasing data highlight the complex interplay between nutrition, metabolic state and the immune response.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 The pathways involved in the induction of T H 17 cells after high-salt intake are related to activation of the p38/mitogen-activated protein kinase, nuclear factor of activated T cells and serum glucocorticoid-regulated kinase pathways (Table 1). [3][4][5][6][7] Notably, recent investigations showed that high-salt intake is involved in the induction of inflammatory reactions through disturbance of the gut microbiota (see recent reviews 2,8 ). In this regard, Wilck et al found that a high-salt diet disturbs the murine gut microbiome and induces neuroinflammation through T H 17 expansion in the EAE-affected murine model.…”
Section: New Findings On the Role Of High-salt Intake In Induction Ofmentioning
confidence: 99%
“…1 In animal models of MS (e.g. [3][4][5][6][7] Notably, recent investigations showed that high-salt intake is involved in the induction of inflammatory reactions through disturbance of the gut microbiota (see recent reviews 2,8 ). 1 In addition to these important findings, new investigations have shown the role of high-salt intake in the pathogenesis of MS through induction of severe neuroinflammation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation